The Effects of Values, Work Centrality, and Organizational Commitment on Organizational Citizenship Behaviors: Evidence from Turkish SMEs - Ucanok, Basak; Karabati, Serdar (Wiley Periodicals, Inc, 2013)
Organizational citizenship behaviors (OCBs) are voluntary contributions of employees not explicitly recognized by the formal reward system and are ultimately critical for sustaining organizational effectiveness (Organ, 1988). The current study aims to investigate the effects of values, work centrality, and organizational commitment on organizational citizenship behaviors in small and medium-sized enterprises (SMEs) in Turkey. It is predicted that work centrality, and affective and normative commitment will increase OCBs along with those values that correspond to OCBs in terms of content. A cross-sectional survey was employed with a convenience sample of 277 SME employees. Data were collected in the midst of the 2008 global financial crisis, which allowed for elaboration on the dynamics of OCBs under difficult periods. The analyses revealed that affective commitment and normative commitment were strong predictors of OCBs. Sportsmanship dimension of citizenship was found to be a function of conservation values, work centrality, and both affective and normative commitment. Findings and suggestions for future research are discussed in light of recent OCB literature and a general HRD perspective.
Keywords: Human-Resource Management; In-Role Performance; Job-Satisfaction; Normative Commitment; Individual-Values; Cultural-Values; Psychological Attachment; Employee Commitment; Antecedents; Continuance